Budidaya Kepiting Soka dengan Metoda Sangkar Massal - Suswanto, Iman; Sirodjul Munir, Achmad Mulyadi (Universitas Tanjungpura, 2018)
Mangrove forest stores enormous economic potential. Economic activity in the mangrove forest village Dabong was catching mangrove clams, fish, shrimp and mud crab. Cultivation of soft-shelled crabs can be done with simple methods such as single cage and mass cage combained moulting pool to facilitate moulting monitor the change of the crab skin. Advantages of moulting pool areÂ ease moulting time monitoring and crab moulting secure against attack other animals.Cultivation of soft-shelled crabs need to be developed extensively for broad economic benefits for the sailor. The results indicate that the development of aquaculture activities shelled crabs using mass cage and moulting pool provide greater benefits. Labor productivity with the same can be increased up to 4- fold compared to a single cage aquaculture way. Excellence moulting pool caused by intensive monitoring for skin exchange both day and night.